Exogenous Application of Calcium Ameliorates Salinity Stress Tolerance of Tomato (Solanum lycopersicum L.) and Enhances Fruit Quality - Md. Moshiul Islam; Khurshida Jahan; Arpita Sen; Tahmina Akter Urmi; M. Moynul Haque; Hayssam M. Ali; Manzer H. Siddiqui; Yoshiyuki Murata (MDPI AG, 2023)
Tomato is affected by various biotic and abiotic stresses, especially salinity, which drastically hinders the growth and yield of tomato. Calcium (Ca) is a vital macronutrient which plays physiological and biochemical roles in plants. Hence, we studied the protective roles of Ca against salinity stress in tomato. There were eight treatments comprising control (nutrient solution), 5 mM Ca, 10 mM Ca, 15 mM Ca, 12 dS m−1 NaCl, 12 dS m−1 NaCl + 5 mM Ca, 12 dS m−1 NaCl + 10 mM Ca and 12 dS m−1 NaCl + 15 mM Ca, and two tomato varieties: BARI tomato-2 and Binatomato-5. Salinity significantly decreased the plant-growth and yield attributes, relative water content (RWC), photosynthetic pigments (SPAD value) and the uptake of K, Ca and Mg in leaves and roots. Salinity-induced oxidative stress was present in the form of increased Na+ ion concentration, hydrogen peroxide (H2O2) content and lipid peroxidation (MDA). Ca application reduced oxidative stress through the boosting of antioxidant enzymatic activity. Exogenous Ca application enhanced proline and glycine betaine content and reduced Na+ uptake, which resulted in the inhibition of ionic toxicity and osmotic stress, respectively. Hence, Ca application significantly increased the growth and yield attributes, RWC, SPAD value, and uptake of K, Ca and Mg. Calcium application also had a significant effect on the fruit quality of tomato and the highest total soluble solid, total sugar, reducing sugar, β-carotene, vitamin C and juice pH were found for the combined application of NaCl and Ca. Therefore, application of Ca reversed the salt-induced changes through increasing osmoprotectants, activation of antioxidants enzymes, and by optimizing mineral nutrient status.